2015
DOI: 10.1186/s12903-015-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Change of periodontal inflammatory indicators through a 4-week weight control intervention including caloric restriction and exercise training in young Koreans: a pilot study

Abstract: BackgroundRecent cross-sectional studies indicate that obesity is a risk factor for periodontal disease. Exercise training in high fat mice or rats can inhibit gingival inflammation effectively. The objective of this human intervention study was to investigate whether short-term weight control could affect periodontal indexes and serum and gingival crevicular fluid (GCF) biomarkers in young Koreans.MethodsForty-one obese volunteers (body mass index (BMI) > 25.0) and 12 normal weight subjects (18.5 ≤ BMI ≤ 23.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…The significant weight loss in the experimental group can be explained by the significant lower intake of total energy (and accordingly macronutrients) which supports studies showing a hyper‐caloric intake under Western diet conditions (López‐Otín, Galluzzi, Freije, Madeo, & Kroemer, ). Besides the specific dietary effects of macro‐ and micronutrients, a lower caloric intake is also associated with better periodontal conditions (Park, Nam, Seo, & Hwang, ). The reason for the significant reduction of total energy in the experimental group might be due to different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The significant weight loss in the experimental group can be explained by the significant lower intake of total energy (and accordingly macronutrients) which supports studies showing a hyper‐caloric intake under Western diet conditions (López‐Otín, Galluzzi, Freije, Madeo, & Kroemer, ). Besides the specific dietary effects of macro‐ and micronutrients, a lower caloric intake is also associated with better periodontal conditions (Park, Nam, Seo, & Hwang, ). The reason for the significant reduction of total energy in the experimental group might be due to different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Weight management in obese subjects has shown a reduction in systemic inflammatory burden as expressed by lower levels of serum cytokines [ 47 , 48 ]. It is also reported that weight control could reduce the amounts of MMP-8, MMP-9, and IL-1 β in GCF of obese subjects with healthy periodontium [ 49 ]. The effect of periodontal therapy on obesity has been reported in recent study [ 50 ]; however, the effect of weight control on GCF cytokine profile in obese patients with CP still needs to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on CR experimen cytokine, chemokine, and metabolic pathways are significantly regulated by CR the aging process. It is expected that a better understanding of senoinflam mechanisms will provide a basis for the discovery of molecular targets that modulate age-related chronic inflammatory conditions and enable the develop effective interventions to delay aging and prevent the occurrence of aging-assoc ├ Human, Mouse, Rat [82,[228][229][230] IL-6 ↑ the intracellular organelles, tissues, and systems, which affects the developmen metabolic disorders. It appears that a repetitive vicious cycle occurs between S dysregulation as proposed in the concept of senoinflammation, and this intera the basis of the aging process and age-related diseases.…”
Section: Sasp Factors Old Cr Species Referencesmentioning
confidence: 99%